Fixed-time autonomous shipboard landing control of a helicopter with external disturbances - Huang, Yanting (2020)
This paper presents a new fixed-time control algorithm to enable autonomous landing of a helicopter onto the ship's deck in the presence of parametric uncertainties and external disturbances. A nonsingular terminal sliding control is implemented as an integral part of the fixed-time control scheme, that guarantees the convergence of system errors to zero in a fixed settling time, however, without the consideration of disturbances. Subsequently, a fixed-time disturbance observer is incorporated into the control structure to efficiently estimate the lumped disturbances including modeling inaccuracies and external perturbations, while reducing the undesired chattering in the control inputs effectively as well. By establishing a relative motion model between the helicopter and the ship, the shipboard landing problem is converted from a general trajectory tracking problem to a more favorable stabilization problem. Based on the fixed-time control scheme in the relative motion model, a relative position controller (RPC) and a relative attitude-altitude controller (RAC) are formulated to guide the helicopter in a dual-phase landing sequence. The RPC will first be implemented to direct the helicopter from its initial position to a hover position above the ship. The next phase involves the application of RAC to guide the helicopter to descend steadily on the ship. Numerical comparative simulations are also carried out to validate the remarkable performance of the proposed control approach.